Shared or Separate? Interreligious Pilgrimage Sites in Lebanon as an Example of Unconventional Social Relations in the Middle East - Bednarska, Julia (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
Followers of various religions with Middle Eastern origins have for centuries made pilgrimages to sites considered sacred by the community to which they belong. However, a certain type of shrine has emerged in the Arab world, and especially in the Middle East, that attracts worshippers from several religious and denominational groups. The existence of interreligious places of worship illustrates an intriguing dimension of the complex social relations in the Middle East, where the boundaries between the ways in which people belonging to different confessions experience religiosity sometimes seem to lose their clarity. The article discusses the creation and operation of interreligious pilgrimage sites, their typology, as well as the shared and distinct rituals practiced by followers of various denominations using the example of Lebanon. It also explores the influence of political and social changes in recent decades on interfaith places of worship. The article outlines the role of these sanctuaries as places for encountering the Other and promoting the idea of coexistence of different Lebanese confessions. Lebanon has been a significant space for interreligious interactions, leading to the creation of numerous interreligious shrines throughout history. Lebanese society has developed shared beliefs regarding the sacred nature of the same places and a belief in the effective intercession of holy figures from different, yet related traditions of monotheistic religions. Although worshippers maintain their unique religious identity, many of the same rituals are performed during pilgrimages across various confessions. Moreover, each group practices specific rituals exclusive to their faith. Interreligious places and expressions of worship can serve as potential spaces for developing national dialogue in Lebanese society. However, for several reasons, they also provoke criticism from some religious groups and leaders. Dynamic social and political processes strongly influence the functioning of interreligious sanctuaries, both positively and negatively. The fate of the Lebanese sanctuaries vividly demonstrates the multidirectional nature of those processes, which have unfolded in Lebanon over the centuries.